Anticandidal Activity of Lipopeptides Containing an LL-37-Derived Peptide Fragment KR12 - Malgorzata Anna Paduszynska; Damian Neubauer; Wojciech Kamysz; Elzbieta Kamysz (Molecules)
Candidiasis belongs to common fungal infections and is usually mild and self-limiting. However, in patients with immunodeficiencies, it can transform into invasive infections with high mortality. Long-term antifungal treatment can lead to the emergence of resistance. The problem is further complicated by the development of fungal biofilm resistant to conventional antimicrobials. Due to a limited choice of available antifungals, the development of novel active agents, such as antimicrobial peptides (AMPs), is highly desirable. Human cathelicidin LL-37 is an intensively studied AMP with a confirmed broad spectrum of antimicrobial activities. Due to the relatively high costs of production, the design of shorter analogs of LL-37 has been recommended. In this study, we synthesized a KR12 amide, KRIVQRIKDFLR-NH2, and its 24 derivatives obtained by substitution with fatty acids. The compounds were tested for their antifungal potential. They exhibited activity against the Candida albicans, C. glabrata, C. tropicalis and C. lipolytica. Five compounds: C10-KR12-NH2, C12-KR12-NH2, C14-KR12-NH2, 2-butyloctanoic acid-KR12-NH2, and 4-phenylbenzoic acid-KR12-NH2 were highly active against planktonic cells. C14-KR12-NH2 demonstrated also activity against C. albicans biofilm cultured on polystyrene for 24, 48 and 72 h. Lipidation has proven to be an effective strategy for improving microbiological activity of the KR12-NH2 peptide.